Protective effect of optic radiation reconstruction against the risk of visual field deficits in anterior temporal lobectomy - Zhi-qiang CUI; Zhi-pei LING; Long-sheng PAN; Xiao-lei CHEN; Qun WANG; Zhi-zhong ZHANG; Ye-qing QI; Xin XU; Zhi-qi1 MAO; Wei-jun WANG; Lu SUN; Xin-guang YU; et al. (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
Objective To explore the clinical value of optic radiation reconstruction in protecting against visual field deficits (VFDs) in anterior temporal lobectomy (ATL). Methods We retrospectively analyzed 24 patients with medically refractory temporal lobe epilepsy undergoing ATL between January 2013 and June 2014. The surgical operations were aided by combining optic radiation reconstruction by diffusion tensor tractography (DTT), microscopy-based neuronavigation and intraoperative MRI (iMRI) techniques. ATL was performed according to the distance between Meyer's loop and temporal pole. The visual fields were examined and seizure outcomes were evaluated by Engel class test in 3-month follow-up. Results The optic radiation was reconstructed in all patients. No bleeding was found in operative site or distant site by iMRI scan. The size of removed temporal lobe was 3.29 cm (1.90-5.10 cm). Visual field testing 3 months after operation showed no VFDs in 16 cases (66.67%) and mild VFDs (< 1/4 quadrant) in 8 cases (33.33% ). One case suffered mild VFD before operation, but did not aggravate after operation. Engel class test showed Engel classⅠin 19 patients (79.17%), class Ⅱ in 4 patients (16.67%) and class Ⅲ in one patient (4.17%). Conclusions For patients with medically refractory temporal lobe epilepsy, the techniques of combining optic radiation reconstruction, microscopy-based euronavigation and iMRI aided in precise mapping could reduce the risk of visual field deficits in anterior temporal lobectomy. DOI: 10.3969/j.issn.1672-6731.2015.09.005